Do Individual Factors, Religiosity Factors, and Demographic Factors Predict Intention to Pay Zakat? - Frank Aligarh; Arif Nugroho; Bayu Sindhu Raharja; Bima Cinintya Pratama; Arya Wanda Wirayuda (Universitas Negeri Surabaya, 2021)
Indonesia has a promising zakat potential; however, the amount of zakat payments is low. The primary objective of this study is to examine what factors influence an individuals intention to pay zakat. This research integrates individual factors, religiosity factors, and demographics factors. About 300 questionnaires were distributed to the respondents in a Muslim-majority area (i.e. Surakarta City), and 223 cases were deemed usable. The data have been analysed using structural equation modelling. This paper finds that attitude, subjective norm, and perceived behaviour control positively affect the intention to pay zakat. Furthermore, religiosity factors and demographic factors also positively affect the intention to pay zakat except for the Islamic education background variable. Theoretically, this study offers a new research model to explain the behaviour of Muzakki in paying zakat. Practically, this study contributes to providing valuable insights for zakat institutions to establish a policy to collect zakat based on individual perspectives.